Sound side joint contact forces in below knee amputee gait with an ESAR prosthetic foot - Karimi, Mohammad Taghi; Salami, Firooz; Heitzmann, Daniel; Alimusaj, Merkur; Putz, Cornelia; Wolf, Sebastian Immanuel (Gait & posture, 2017)
The incidence of knee and hip joint osteoarthritis in subjects with below knee amputation (BK) appears significantly higher compared to unimpaired subjects, especially in the intact side. However, it is controversial if constant higher loads on the sound side are one of the major factors for an increased osteoarthritis (OA) incidence in subjects with BK, beside other risk factors, e.g. with respect to metabolism. The aim wasto investigate joint contact forces (JCF) calculated by a musculoskeletal model in the intact side and to compare it with those of unimpaired subjects and to further elucidate in how far increased knee JCF are associated with increased frontal plane knee moments. A group of seven subjects with BK amputation and a group of ten unimpaired subjects were recruited for this study. Gait data were measured by 3D motion capture and force plates. OpenSim software was applied to calculate JCF. Maximum joint angles, ground reaction forces, and moments as well as time distance parameters were determined and compared between groups showing no significant differences, with some JCF components of knee and hip even being slightly smaller in subjects with BK compared to the reference group. This positive finding may be due to the selected ESAR foot. However, other beneficial factors may also have influenced this positive result such as the general good health status of the subjects or the thorough and proper fitting and alignment of the prosthesis.
Available online 8 August 2017
Gesehen am 26.06.2018